Gene-Gene Associations with the Susceptibility of Kawasaki Disease and Coronary Artery Lesions. - Ho-Chang Kuo; Jen-Chieh Chang; Mindy Ming-Huey Guo; Kai-Sheng Hsieh; Deniz Yeter; Sung-Chou Li; Kuender D Yang (PLoS ONE, 2015)
Kawasaki disease (KD) is a systemic vasculitis primarily affecting children < 5 years old. Genes significantly associated with KD mostly involve cardiovascular, immune, and inflammatory responses. Recent studies have observed stronger associations for KD risk with multiple genes compared to individual genes. Therefore, we investigated whether gene combinations influenced KD susceptibility or coronary artery lesion (CAL) formation. We examined 384 single-nucleotide polymorphisms (SNPs) for 159 immune-related candidate genes in DNA samples from KD patients with CAL (n = 73), KD patients without CAL (n = 153), and cohort controls (n = 575). Individual SNPs were first assessed by univariate analysis (UVA) and multivariate analysis (MVA). We used multifactor dimensionality reduction (MDR) to examine individual SNPs in one-, two-, and three-locus best fit models. UVA identified 53 individual SNPs that were significantly associated with KD risk or CAL formation (p < 0.10), while 35 individual SNPs were significantly associated using MVA (p ≤ 0.05). Significant associations in MDR analysis were only observed for the two-locus models after permutation testing (p ≤ 0.05). In logistic regression, combined possession of PDE2A (rs341058) and CYFIP2 (rs767007) significantly increased KD susceptibility (OR = 3.54; p = 4.14 x 10(-7)), while combinations of LOC100133214 (rs2517892) and IL2RA (rs3118470) significantly increased the risk of CAL in KD patients (OR = 5.35; p = 7.46 x 10(-5)). Our results suggest varying gene-gene associations respectively predispose individuals to KD risk or its complications of CAL.